2000
DOI: 10.1046/j.1365-313x.2000.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel aldose/aldehyde reductase protects transgenic plants against lipid peroxidation under chemical and drought stresses

Abstract: Rapid accumulation of toxic products from reactions of reactive oxygen species (ROS) with lipids and proteins significantly contributes to the damage of crop plants under biotic and abiotic stresses. Here we have identified a stress-activated alfalfa gene encoding a novel plant NADPH-dependent aldose/aldehyde reductase that also exhibited characteristics of the homologous human enzyme. The recombinant alfalfa enzyme is active on 4-hydroxynon-2-enal, a known cytotoxic lipid peroxide degradation product. Ectopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(113 citation statements)
references
References 34 publications
4
106
1
1
Order By: Relevance
“…Recently, an aldehyde reductase (37) has been identified in both the mitochondria and the cytoplasm that reacts with HNE. A glutathione S-transferase, which uses HNE as a substrate, has been identified in mammalian mitochondria (38,39) and in the monocot Sorghum bicolour (40).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an aldehyde reductase (37) has been identified in both the mitochondria and the cytoplasm that reacts with HNE. A glutathione S-transferase, which uses HNE as a substrate, has been identified in mammalian mitochondria (38,39) and in the monocot Sorghum bicolour (40).…”
Section: Discussionmentioning
confidence: 99%
“…Oberschall et al (27) have reported that overexpression of an alfalfa AKR contributed to improve plant tolerance to chemical and drought stresses through enhanced reduction of reactive aldehydes produced during lipid peroxidation. Interestingly, the alfalfa AKR is a homolog of AtChlAKR (At2g37770); the physiological significance of this class of AKR in plant species might therefore be the detoxification of reactive aldehydes.…”
Section: Aor Adr and Akr Cooperatively Scavenge Reactive Carbonyls mentioning
confidence: 99%
“…In plants, very few enzymatic pathways that reduce aldehyde accumulation have been defined. Two enzymes including soybean aldose/aldehyde reductase and Arabidopsis alkenal, a, b-hydrogenase have been shown to participate in the reduction of aldehydes (Oberschall et al 2000;Mano et al 2002). In rice, two acetaldehyde-oxidizing ALDHs (ALDH1a and ALDH2a) were characterized.…”
Section: Introductionmentioning
confidence: 99%